2015
DOI: 10.1007/s11469-015-9584-8
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and Barriers to Services for Immigrant Fathers Raising Children with Developmental Disabilities

Abstract: This narrative review examines research on the experiences of immigrant fathers raising children with developmental disabilities, and considers the findings within the Canadian context. Applying Green, Johnson & Adams’ (Journal of Chiropractic Medicine, 5(3), 101–117, 2006) methodology, a step-by-step process was followed to conduct the review. Four databases (PsychINFO, PubMed, CINAHL and Sociological Abstracts) were used for the search. A total of 39 articles were found to be relevant after applying the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…The mothers' psychological and physical health are negatively impacted, with mothers experiencing increased stress, burn-out, and other health ramifications. Elsewhere we have reported that immigrant parents of children with disabilities in Canada generally experience significant challenges in structural support, instrumental support, emotional support, and perception of support (Khanlou et al, 2015a(Khanlou et al, , 2015b. Our current study further supports this, as we found that mothers' health was viewed as holistic and tied to family health.…”
Section: Discussionsupporting
confidence: 82%
“…The mothers' psychological and physical health are negatively impacted, with mothers experiencing increased stress, burn-out, and other health ramifications. Elsewhere we have reported that immigrant parents of children with disabilities in Canada generally experience significant challenges in structural support, instrumental support, emotional support, and perception of support (Khanlou et al, 2015a(Khanlou et al, , 2015b. Our current study further supports this, as we found that mothers' health was viewed as holistic and tied to family health.…”
Section: Discussionsupporting
confidence: 82%
“…Attending medical appointments for a child with a disability was a challenge due to inconvenient public transportation. This is of special relevance because new immigrant families often settled in peripheral suburbs where the rent was cheaper, but health and social services were mainly located in the city center (Khanlou, Haque, et al, ; Khanlou, Mustafa, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Parents were isolated from their extended family and community (Blanche et al, ). Khanlou, Mustafa, and colleagues () found that immigrant parents felt strongly that they were social outcasts not only by the community, but by their families, who tended to blame them for their child’s condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a child with developmental disability imposes a severe burden on parents. 1 Examples of problems associated with parenting a child with a developmental disability may include difficulties in responding to child behavior problems, 2 stigma among family caregivers, 3 financial and social barriers, 4 and difficulties in preparing the child during transitional periods such as transition to school. 5 Disabilities in children may include but are not limited to autism spectrum disorder, learning disability, chronic cognitive or health impairment, and attention deficit disorder.…”
Section: Introductionmentioning
confidence: 99%